2021
DOI: 10.1292/jvms.21-0158
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of placentome in Korean water deer <i>Hydropotes inermis argropus</i>

Abstract: The placenta of the Korean water deer was anatomically examined to accumulate basic information regarding its reproductive system. The convex placentomes with five to nine welldeveloped pedicles were observed in the whole uterine horns, and therefore, the placenta was classified as oligocotyledonary. The evidence indicating the migration of binucleate cells (BNCs) from trophectoderm to the uterine epithelium led to the histological classification of the placenta as synepitheliochorial. The number of fetuses wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Promotes the proliferation of in other words, it is thought that changes in the uterus of the sika deer stabilize the villus earlier than changes in the uterine tissue of the water deer. According to the research results of Sohn et al, 2021, in the case of water deer, the placenta is classified as oligocotyledon, similar to other plumids with 6-8 placentas, and the villus is well developed, so a distinct glands zone is visible in each villus (Yanagawa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promotes the proliferation of in other words, it is thought that changes in the uterus of the sika deer stabilize the villus earlier than changes in the uterine tissue of the water deer. According to the research results of Sohn et al, 2021, in the case of water deer, the placenta is classified as oligocotyledon, similar to other plumids with 6-8 placentas, and the villus is well developed, so a distinct glands zone is visible in each villus (Yanagawa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be confirmed that there is a difference in the shape of the uteroplacental junction that spreads from the uterus to the placenta. These morphological differences in the uterus and the overall tissue reorganization formed during the estrus period of the sika deer can be seen as a unique shape unique to the sika deer, and may differ depending on the Cervidae family (Wooding et al, 2018;Sohn et al, 2021). However, most sika deers' wombs rapidly remodel Therefore, through this study, it is believed that the action of hormones related to the estrus period of sika deer and the activity of genes related to uterine remodeling act differently depending on the presence or absence of pregnancy, which will play a role in determining the timing of pregnancy in sika deer in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Placentome morphology has been studied in many domestic and wild ruminant species, including domestic cattle (Laven and Peters 2001), water buffalo (Abd-Elnaeim et al 2003), sheep and goat (Mossman 1987;Hradecky et al 1988;Kashoma and Luziga 2019), deer (Sohn et al 2021) and antelope (Hradecky et al 1988;Benirschke 2005). However, the number, size, and shape of placentomes depend on species and breeds (Schlafer et al 2000;Laven and Peter 2001;Schmidt et al 2006;Lui et al 2010).…”
mentioning
confidence: 99%